Hip Arthroplasty with Increased Expectancy - Thiele, Kathi; Hube, Robert (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
The patientʼs demands and expectations after total hip arthroplasty have increased significantly. In particular, the athletic function is the focus of the patientʼs interest, whereby not the basic sports ability is inquired, but also the achievable sports level. The benefits of increased activity with a reduction in cardiovascular mortality and the minimization of osteoporosis risk are contrasted by amplified wear followed by prosthesis loosening. Activities are categorized in low-, intermediate- and high-impact kind of sport. Patient-based influencing factors such as physical condition and expertise in his sport, as well as the self-reference of the surgeon to the desired sport influence the recommendation and advice of the patient. Innovations in prosthesis design and materials technology allow meeting patientʼs expectations and aiming to improve the return to sport. After total hip arthroplasty, the majority of preoperatively active patients return to athletic activity, although there is a tendency to shift from “high-impact” to “low-impact” sports. The currently recommended sports include swimming, cycling, Nordic walking, sailing, golf, hiking, dancing and cross-country skiing. A limited recommendation exists for tennis (single), alpine skiing, mountain hiking and sportive running. Not recommended are marathon, football, handball, volleyball, basketball, martial arts, high jump, water skiing and rock climbing. The recommendations are based primarily on expert opinions and are in a progressive extension including “high-impact” sports.
Keywords: sports after hip arthroplasty; high impact; low impact; wear; joint load